Community service in Kecamatan Patampanua: Improving community's economy and prosperity through the establishment of pisang sale's UMKM. (February 2019) - Dirpan, A; Heniwati, E; Patawari, M Y; Birawida, A B
Abstract: Collaboration, among the Hasanuddin University Regional Partnership Program (PKW), POLITANI, and the Pinrang District Government, has carried out community service activities with the aim of overcoming the problems in the Patampanua District, in particular, Desa Sipatuo. Knowledge and skills to utilize the district's surrounding natural resources are essential for a community to improve their economy and welfare as one of the solutions to decrease poverty. This activity aims to increase the knowledge and skills of communities in the Desa Sipatuo about processing bananas into banana sale products. This activity was carried out in Desa Sipatuo on July 24-26, 2018 by involving the community as a target audiences. The method used is counseling, demonstration with pre-activity events, implementation and evaluation of knowledge. The results are the community's knowledge about banana's nutritional content and its processed products, namely the sale pisang increases. The society favored with the taste, color, flavor, and texture of banana sale product.